New subspecies of Eumerus aristatus Peck, 1969 (Diptera, Syrphidae) from Karabas Mountains (Eastern Kazakhstan) - Златанов, Б.В. (Fundamental and Experimental Biology, 2023)
In 2022, in the course of studying the entomofauna of the Tarbagatai State National Natural Park in the southern spur of the Tarbagatai Ridge in the Karabas Mountains, several hover flies (Syrphidae) of the genus Eumerus with a lanceolate-apically widened arista were caught, which are described in this paper as a new subspecies of Eumerus aristatus Peck, 1969. The male of the described subspecies differs from E. aristatus in the presence of plaque and the color of the hairs on the head, the location of the ocellar triangle, the shape and color of the antennae, and the color of the tint of the body color.